1994
DOI: 10.5144/0256-4947.1994.503
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Prevalence of Hepatitis Delta Virus in Eastern Saudi Arabia

Abstract: Four hundred and eleven (411) confirmed hepatitis B surface antigen (HBsAg) positive individuals were tested for hepatitis delta antibodies (anti HDV) by the enzyme immunoassay method (EIA) from June 1988 through December 1993. An overall prevalence rate of 4.87% was recorded while rates for liver diseased patients, subjects on hemodialysis programs, intravenous drug addicts and blood donors showed 7.69%, 6.85%, 5.77% and 2.75% respectively. Breaking down rates according to the country of origin of our subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
11
2
Order By: Relevance
“…The above studies and the present one indicate that pattern of endemicity of HAV infection is shifting in KSA (Tufenkeji, 2000). On contrary, seroprevalence study in Eastern region of KSA (Dammam) showed that hepatitis A virus infection starts dramatically high in school-age children, and then rise gradually with an increase in age reflecting high endemic of HAV in this region (Fathalla et al, 2000).…”
Section: Discussioncontrasting
confidence: 44%
“…The above studies and the present one indicate that pattern of endemicity of HAV infection is shifting in KSA (Tufenkeji, 2000). On contrary, seroprevalence study in Eastern region of KSA (Dammam) showed that hepatitis A virus infection starts dramatically high in school-age children, and then rise gradually with an increase in age reflecting high endemic of HAV in this region (Fathalla et al, 2000).…”
Section: Discussioncontrasting
confidence: 44%
“…This prevalence for HBsAg is lower than that reported in the eastern region (6.7%) and the southwestern region (5.4%), but higher than that reported from the central region (1.5%) of Saudi Arabia. 13,14 This prevalence is also higher than that reported from Western countries (0.1-0.5%), but lower than that from the Far Eastern countries. 15,16 The prevalence of HBsAg among blood donors has been found to be 3.8% in Syria, 9.8% in Yemen, 1.2% in Egypt, and 1.2-1.7% in India.…”
Section: Discussionmentioning
confidence: 60%
“…This increase was due to resistance of enterovirus in the environment and the habits of the population studied. However, FATHALLA et al 5 and PAPAEVANGELOU et al 12 did not observed the seasonal variation in the prevalence of hepatitis A in Saudi Arabia and Greece, respectively. This study was carried out to investigate any seasonal variation in the occurrence of acute cases of hepatitis A in the city of Rio de Janeiro, Brazil.…”
Section: Introductionmentioning
confidence: 92%